Engineering Synthetic Microbial Communities: Diversity and Applications in Soil for Plant Resilience - Arneeb Tariq; Shengzhi Guo; Fozia Farhat; Xihui Shen (Agronomy)
Plants host a complex but taxonomically assembled set of microbes in their natural environment which confer several benefits to the host plant including stress resilience, nutrient acquisition and increased productivity. To understand and simplify the intricate interactions among these microbes, an innovative approach—Synthetic Microbial Community (SynCom)—is practiced, involving the intentional co-culturing of multiple microbial taxa under well-defined conditions mimicking natural microbiomes. SynComs hold promising solutions to the issues confronted by modern agriculture stemming from climate change, limited resources and land degradation. This review explores the potential of SynComs to enhance plant growth, development and disease resistance in agricultural settings. Despite the promising potential, the effectiveness of beneficial microbes in field applications has been inconsistent. Computational simulations, high-throughput sequencing and the utilization of omics databases can bridge the information gap, providing insights into the complex ecological and metabolic networks that govern plant–microbe interactions. Artificial intelligence-driven models can predict complex microbial interactions, while machine learning algorithms can analyze vast datasets to identify key microbial taxa and their functions. We also discuss the barriers to the implementation of these technologies in SynCom engineering. Future research should focus on these innovative applications to refine SynCom strategies, ultimately contributing to the advancement of green technologies in agriculture.